The Effect of Epidermin Produced by Local Isolate of S. Epidermidis on Antibacterial Activity of Some Agents Used in Wounds and Burns Treatment - Al-Ibadi, Munira CH; Abdl-Majeed, Farah H; Fadhil, Ayad M Ali (Al-Nahrain Journal of Science, 2018)
Epidermin of local Staphylococcus epidermidis isolate was tested individually and in combination with some agents(that used in treatment of wounds and burns)against pathogenic bacteria (Staphylococcus aureus and Escherichia coli), by using agar spot method , and agar diffusion method respictivelly . Results showed that, S. epidermidis isolate had the ability to produced epidermin and antibacterial activity toward S. aureus, whereas E. coli was not inhibited. Results of synergestic effect of pure epidermin with some agents, showed that, Samacyclin(with and without epidermin) was the most effective agent, Nifusin was the second and Silverin, acetic acid (6%) and iodine (10%) was the least effective agents.